Failure analysis on the drillpipe due to the twist-off - Mohd Iqbal, Mohd Zolkepeli (2008)
This thesis reports on the design and analysis for failure at three different drill pipes. When drilling boreholes, for example in the Oil & Gas industry, a hole is drilled into the ground which can be several kilometers long. One of main type of problem that can occur while drilling is the torque on the drill pipe can cause it to break (called twist-off). This problem results in drilling delays. Twist-offs also usually results in loss of expensive equipment. Therefore, ALGOR software has been use as the FEA tool to do the analysis to reduce this problem. Six different values of torque range from 2000 N.m to 3000 N.m is applied to the end of the pipe stand which is consist of three assembly of pipes. The materials of the pipe have been chosen are AISI 1010, ASTM A36 and AISI 4150 steels that have different mechanical properties the see the differences. The test results show that AISI 4150 is the most suitable material to use which gives 2800 N.m torque value before it starts to fail. Meanwhile, a constant pattern of failure has determined for these three pipes at the same location of the second engaged thread of the pipe assembly, between the male and female thread at the joint. For improvement, to see the differences from another point of view, the analysis for this drill pipe design is suggested to do with different thickness and length in order to analyze how much the maximum allowable torque value can be applied to the pipe before it starts to fail.